Лінгвостилістика та функції перифраз у сучасному публіцистичному дискурсі - Підкамінна, Людмила; Pidkaminna, Liudmyla (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано структурно-семантичні та функціонально-стилістичні особливості перифраз у сучасному публіцистичному дискурсі, виявлено їхні естетико-образні характеристики та механізми творення, виокремлено та досліджено основні тематичні групи, у межах яких відбувається перефразування. The structural and semantic, functional and stylistic features of paraphrase in modern publicistic discourse have been analyzed, their aesthetic and imaginative descriptions and mechanisms of creation have been identified; the main thematic groups within which a paraphrasing takes place have been examined in the article. The results of the study of the functioning of the trope in modern publicistic discourse give reason to believe that the paraphrase is a semantic equivalent of the described phenomenon; it has emotional and evaluative character and promotes the expression of speech. Active use of paraphrase in the language of journalism is predetermined by the ability of trope to be an instrument of influence on the reader.
Lingvostylistics and Functions of Paraphrase in Modern Publicistic Discourse
Keywords: перифраза; публіцистичний дискурс; семантичний еквівалент; стилістичні функції; структурні моделі перифраз; paraphrase; publicistic discourse; semantic equivalent; stylistic functions; structural models of paraphrase